EVALUASI NILAI KECERNAAN IN VITRO DAUN KELAPA SAWIT TERFERMENTASI MA-11 SEBAGAI PAKAN TERNAK - Sutrisno, Joko; Sukaryani, Sri; Suci Purwati, Catur (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2025)
ABSTRACT This research to determine the effect of fermentation incubation using MA-11 on the in vitro digestibility value of dry matter and organic matter of palm leaves. The design used is a Complete Random Design (RAL) unidirectional pattern with 4 treatments and and 3 replicates. The treatment is T0: oil palm leaves without fermentation; T1: oil palm leaves fermented using MA-11, incubated for 3 days, T2: oil palm leaves fermented using MA-11, incubated for 6 days. T3: palm leaves are fermented using MA-11, incubated for 9 days. The variables observed included the digestibility value of dry materials and organic materials. The data obtained was then analyzed using Variance Analysis (Anova) with a unidirectional pattern RAL and if there was a difference between the treatments, further tests were carried out using the Duncan't Multiple Region Test (DMRT). The results showed that fermentation using MA-11 with an incubation period of 0 – 9 days had a very significant effect on increasing the digestibility value of dry and organic materials (P<0.01). This research can conclude that the fermentation of oil palm leaves using MA-11 with an incubation period of 0 – 9 days can increase the digestibility value of dry matter and organic matter, and the longer the incubation time in fermentation, the more it increases the digestibility value of dry matter and organic matter.